Treatment of purulous-inflammatory complications of injuries and diseases of pelvic bones - Trufanov, I. I.; Klyatsky, Yu. P.; Tribushny, O. V.; Kosilo, V. V.; Klyatskа, L. I.; Yurchenko, P. G.; Труфанов, Іван Іванович; Кляцький, Юрій Пантелійович; Трибушний, Олег Володимирович; Косило, Василь Васильович; Кляцька, Лариса Іванівна; Юрченко, П. Г. (My University, 2023)
Purpose of the study. By analyzing clinical mistakes and the possibility of purulentinflammatory complications during operative treatment and postoperative management of patients with fractures bones of the pelvis, as well as to determine methods of diagnosis, treatment and ways of prevention traumatic sacroiliitis. Materials and methods. In the period from 2017 to 2022 in the bone-purulent surgery department of Zaporizhzhia city clinical hospital № 9 treated 9 patients with purulent processes in of the pelvic region, 6 (66,3%) of them were men, and 3 (33,4%) were women. With postoperative osteomyelitis, which occurred after osteosynthesis with plates of multiple pelvic bone fractures, 4 (44,5%) patients were treated. Conservative therapy with sacroiliitis, the cause of which was abortion, received by 2 (22,2%) women, 1 (11,1%) patient suffered from right-sided sacroiliitis since childhood and repeatedly operated, and 2 (22,2%) men were treated with cause of sacroiliitis, which occurred after slaughter of the sacroiliac joint area.Мета роботи. Проаналізувати клінічні помилки і можливість виникнення гнійно-запальних ускладнень при оперативному лікуванні та післяопераційному веденні хворих з переломами кісток тазу, а також визначити методи діагностики, лікування та шляхи профілактики сакроілеїтів травматичного характеру. Матеріали і методи. В період з 2017 по 2022 роки у відділенні кістково-гнійної хірургії 9 міської клінічної лікарні отримували лікування 9 хворих з гнійними процесами в області таза, з них чоловіків було 6 (66,3%), а – жінок 3 (33,4%). З післяопераційним остеомієлітом, який виник після остеосинтезу пластинами множинних переломів кісток таза, лікувалося 4 (44,5%) пацієнта. Консервативну терапію з сакроілеїтом, причиною якого був аборт, отримували 2 (22,2%) жінки, 1 (11,1%) хворий страждав на правосторонній сакроілеїт з дитячого віку і неодноразово оперувався та 2 (22,2%) чоловіка проходили лікування з приводу сакроілеїту, який виник після забою області крижово-клубового суглобу.
Лікування гнійно-запальних ускладнень пошкоджень та захворювань кісток таза
Keywords: postoperative osteomyelitis of the pelvis; sacroiliitis; surgical treatment; antibacterial therapy; післяопераційний остеомієліт таза; сакроілеїт; оперативне лікування; антибактеріальна терапія